Hubungan Dukungan Keluarga dengan Respon Cemas pada Anak Usia Sekolah (6-12 Tahun) Saat Dilakukan Pemasangan Infus - Siska Ayu Ningsih (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2019)
Hospitalization in pediatric patients will cause children to feel anxious and stressed in various conditions. The purpose of this study was to determine the relationship of family support to anxious responses in school-age children (6-12 years) when an IV was placed in the emergency room at Rafflesia Bengkulu Hospital. This research is a descriptive analytic study with cross sectional approach. A sample of 78 children were placed on an IV line, samples were taken using accidental sampling technique. Data were obtained using a family support questionnaire and anxiety observation sheets. Bivariate analysis uses the Chi Square formula. Univariate analysis results found 57.7% of family support is good while 42.3% of family support is not good, while the level of anxiety of children is 17.9% not worried, 43.6% mild anxiety and 38.5% moderate anxiety. Bivariate analysis found Ï value 0,000, which means there is a relationship between family support and the level of anxiety of children. Conclusion, there is a significant relationship between family support and the level of anxiety of school-age children (6-12 years) when infusion is placed.Â Keyword: Family Support, Child Anxiety, Hospitalization